A comparison of the surface nanostructure from two different types of gram-negative cells: Escherichia coli and Rhodobacter sphaeroides. (May 2015) - Oestreicher, Zachery; Taoka, Azuma; Fukumori, Yoshihiro
Highlights: We used the high-speed atomic force microscope to examine E. coli and R. sphaeroides. We examine the nano-structure of the outer surface of living bacterial cells. Both types of cells contain an array of ordered holes that cover the outer surface. The size and pattern of the holes is similar to what was found on M. magneticum. This ordered array of holes is a structure that may be common to Proteobacteria . Abstract: Bacteria have been studied using different microscopy methods for many years. Recently, the developments of high-speed atomic force microscopy have opened the doors to study bacteria in new ways due to the fact that it uses much less force on the sample while imaging. This makes the high-speed atomic force microscope an indispensable technique for imaging the surface of living bacterial cells because it allows for the high-resolution visualization of surface proteins in their natural condition without disrupting the cell or the activity of the proteins. Previous work examining living cells of Magnetospirillum magneticum AMB-1 demonstrated that the surface of these bacteria was covered with a net-like structure that is mainly composed of porin molecules. However, it was unclear whether or not this feature was unique to other living bacteria. In this study we used the high-speed atomic force microscope to examine the surface of living cells of Escherichia coli and Rhodobacter sphaeroides to compare their structure with that of M. magneticum . Our research clearly demonstrated that both of these types of cells have an outer surface that is covered in a network of nanometer-sized holes similar to M. magneticum . The diameter of the holes was 8.0 ± 1.5 nm for E. coli and 6.6 ± 1.1 nm for R. sphaeroides . The results in this paper confirm that this type of outer surface structure exists in other types of bacteria and it is not unique to Magnetospirillum .